Tobacco Smoke and Inhaled Drugs Alter Expression and Activity of Multidrug Resistance-Associated Protein-1 (MRP1) in Human Distal Lung Epithelial Cells in vitro - Selo, Mohammed Ali; Delmas, Anne-Sophie; Springer, Lisa; Zoufal, Viktoria; Sake, Johannes A.; Clerkin, Caoimhe G.; Huwer, Hanno; Schneider-Daum, Nicole; Lehr, Claus-Michael; Nickel, Sabrina; Langer, Oliver; Ehrhardt, Carsten (Frontiers in Bioengineering and Biotechnology, 2020)
Multidrug resistance-associated protein-1 (MRP1/ABCC1) is highly expressed in human lung tissues. Recent studies suggest that it significantly affects the pulmonary disposition of its substrates, both after pulmonary and systemic administration. To better understand the molecular mechanisms involved, we studied the expression, subcellular localisation and activity of MRP1 in freshly isolated human alveolar epithelial type 2 (AT2) and type 1-like (AT1-like) cells in primary culture, and in the NCI-H441 cell line. Moreover, the effect of cigarette smoke extract (CSE) and a series of inhaled drugs on MRP1 abundance and activity was investigated in vitro. MRP1 expression levels were measured by q-PCR and immunoblot in AT2 and AT1-like cells from different donors and in several passages of the NCI-H441 cell line. The subcellular localisation of the transporter was studied by confocal laser scanning microscopy and cell surface protein biotinylation. MRP1 activity was assessed by bidirectional transport and efflux experiments using the MRP1 substrate, 5(6)-carboxyfluorescein (CF) (formed intracellularly from 5(6)-carboxyfluorescein-diacetate (CFDA)) in AT1-like and NCI-H441 cell monolayers. Furthermore, the effect of CSE as well as several bronchodilators and inhaled corticosteroids on MRP1 abundance and CF efflux was investigated. MRP1 protein abundance increased upon differentiation from AT2 to AT1-like phenotype, however, ABCC1 gene levels remained unchanged. MRP1 abundance in NCI-H441 cells were comparable to those found in AT1-like cells. The transporter was detected primarily in basolateral membranes of both cell types which was consistent with net basolateral efflux of CF. Likewise, bidirectional transport studies showed net apical-to-basolateral transport of CF which was sensitive to the MRP1 inhibitor MK-571. Budesonide, beclomethasone dipropionate, salbutamol sulphate and CSE decreased CF efflux in a concentration-dependent manner. Interestingly, CSE increased MRP1 abundance, whereas budesonide, beclomethasone dipropionate, salbutamol sulphate did not have such effect. CSE and inhaled drugs can reduce MRP1 activity in vitro, which implies the transporter being a potential drug target in the treatment of chronic obstructive pulmonary disease (COPD). Moreover, MRP1 expression level, localisation and activity were comparable in human AT1-like and NCI-H441 cells. Therefore, the cell line can be a useful alternative in vitro model to study MRP1 in distal lung epithelium.